Pelatihan dan Edukasi Siaga Bencana Gempa Bumi Kepada Anak-anak di SDN Wonocolo 1 Sidoarjo - Wijayanti, Regita Faridatunisa; Putra, Angga Pratama; Hayati, Nurul; Agustini, Maria; Bambang Sigit Sucahyo, Mikael; Taufik, Moh; Novia Santika, Desna; Armadana, Aldi; Maulana, Muhammad Zaki; Aulia Febrianti, Andi Eka (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2024)
The important role of training and education regarding earthquake disasters and early disaster mitigation is the main basis for this community service activity. Earthquake training and education for children at SDN Wonocolo 1 Sidoarjo includes delivering material about earthquake signs, types of earthquakes, mitigation steps that need to be taken when an earthquake occurs, and the impacts caused by earthquake disasters. Apart from that, we also carried out evacuation practices during an earthquake and created an evacuation route at SDN Wonocolo 1 Sidoarjo. With this early training and education, it is hoped that children can understand the concept of earthquake disasters and know what to do when an earthquake occurs, so as to reduce panic and loss of life. The steps in this training and education activity include preparing and determining activities and locations for implementing PKM, creating materials and planning activities that will be delivered to children at SDN Wonocolo 1 Sidoarjo regarding earthquake disasters and how to mitigate them. Furthermore, the training and education activities were carried out at SDN Wonocolo 1 Sidoarjo. Based on comments and reviews from children, it can be concluded that students at SDN Wonocolo 1 Sidoarjo have a lot of understanding about earthquake disasters and the steps that must be taken when a disaster occurs. Keywords: Elementary School Children, Earthquake Disaster, Education, Training, Disaster Preparedness